Estudo do processo integrado de fermentação alcoólica extrativa com CO2 com desidratação por adsorção e recuperação por absorção - Santos, Mayara Vieira (Universidade Federal de São Carlos, 2022)
To minimize the effects of ethanol inhibition, increase productivity, and reduce energy and environmental footprint, different strategies of ethanol removal by gas stripping with CO2 during alcoholic fermentation have been studied. However, there are a few studies on how to efficiently recover the ethanol removed by stripping, which becomes difficult the application of this technique. In the present work, an integrated process of ethanol production by extractive fermentation with CO2 stripping and ethanol recovery by the association of adsorption and absorption processes was developed. Firstly, an analytical methodology based on the combination of Fourier transform mid-infrared spectroscopy (FT-MIR) with the partial least squares multivariate regression (PLS) method was developed to monitor the gas phase containing water and ethanol. Then, the water and ethanol adsorptive capacities of the 3A (Z1, Z2, and Z3) zeolites and cassava sago adsorbents were evaluated in an up-flow packed column to select the most suitable adsorbent for dehydration of the gas stream from stripping of hydroalcoholic solutions and extractive fermentations. The next step was to evaluate different strategies of association of the adsorption and absorption (with monoethilene glycol, MEG) processes using extractive fermentation experiments operated in fed-batch mode using different substrate concentrations in the feed stream. Regarding adsorption, zeolite 3A (Z3) stood out for adsorbing all water from the gas stripping stream for the longest time period (10 h), having the highest affinity for water (0.1231 gW.gAdsorbent-1), and the lowest affinity for ethanol among the evaluated zeolites. While sago adsorbent, despite having a shorter break-up time and lower affinity for water, it was the adsorbent that did not interact with ethanol. The association of adsorption (with a fixed bed column filled with 3A zeolite) and subsequent absorption (using absorbers connected in series containing MEG) was the best combination of operations studied. This configuration provided the highest overall ethanol recovery (96.3% for hydroalcoholic solutions and 100% for extractive batch fermentation) and considerable dehydration of the gas stream (100% for hydroalcoholic solutions and 91% for extractive batch fermentations). The integrated process of fed-batch extractive fermentation and recovery by adsorption and absorption allowed the conversion of 240 g L-1 of the substrate into ethanol of 117.6 g L-1 (14.9 °GL). This value was 47% higher compared to those obtained in conventional fed-batch fermentation (operated in similar industrial conditions). The combination of the adsorption and subsequent absorption processes was an excellent strategy for dehydration of the fermentation gas stream fed with substrate concentration value similar to those found in industrial facilities (100%) and extractive fermentation with high substrate load (99.4%), and ethanol recovery in both fermentation conditions. The system was able to recover all the ethanol removed by the stripping stream. The combined process of fed-batch fermentation, gas stripping with CO2, and ethanol recovery proved to be a promising process since a greater amount of substrate can be fed into the fermentation with constant ethanol removal, directly influencing the increase in ethanol productivity. Furthermore, the combination of adsorption and absorption processes promoted the recovery of all ethanol, which directly impacts on the global increases in industrial production capacity.
Study of the integrated process of extractive alcoholic fermentation with CO2 with dehydration by adsorption and recovery by absorption
Keywords: Etanol; Fermentação extrativa; Stripping por CO2; Recuperação de etanol; Adsorção gasosa; Absorção gasosa; Integração de processos; Ethanol; Extractive fermentation; Stripping by CO2; Ethanol recovery; Gas adsorption; Gas absorption; Process integration; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA